Analysis of Pedestrian Behavior in the City of Pila - Piotr Gorzelańczyk; Jakub Bazela; Tomáš Kalina; Martin Jurkovič (Communications - Scientific letters of the University of Zilina, 2022)
Every year, many people lose their health and/or lives on Polish roads. One of the reasons for this is behavior of pedestrians at pedestrian crossings, which affects the road safety. The aim of the article was to conduct experimental research, the idea of which was to study the behavior of pedestrians at pedestrian crossings in the city of Pila, the results of which can be applied to Poland. During the research, the behavior of pedestrians and the impact on the probability of a road accident were analyzed. Undoubtedly, the prevailing epidemic, during which people are in many respects limited, had an impact on the results obtained, therefore the number of people at the analyzed crossings may have decreased. The conducted research confirmed the Police statistical data that the most dangerous crossings for pedestrians are those without traffic lights.